(untitled) (World Economics and Finance Bulletin, 2022)
The article analyzes the current state and problems that hinder the development of investment and construction activities and evaluates the effectiveness of this area of activity against the background of problems with the use of the Investment Fund. For the first time, a methodical approach to assessing the share of imports in investments for the purchase of machinery, equipment and vehicles as a type of fixed assets of the domestic economy is substantiated; the results of the corresponding calculations are presented. The ways of solving urgent problems in the field of investment and construction activities, as well as the requirements that should be presented to the formation of the state investment and construction policy are outlined.